Trophic State of Embung AKAPPayung Sekaki DistrictCity of Pekanbaru Based on Trophic Index (TRIX) By: - Siahaan, Oloan; Siagian, Madju; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractTrophic Index (TRIX) can be used to determine the trophic state of waters based on chemical and biological parameters. To understand the trophic state of the Embung AKAPwaters based on Vollenweider’s Trophic Index (TRIX), a research has been conducted in November-December 2018. There were three station, namelyStation 1 (inlet), Station 2 (in the middle of Embung AKAP), and Station 3 (outlet).Sampling were conducted 3 times, once/week.Water quality parameters measured were DIN, total phosphorus, dissolved oxygen, chlorophyll-a, transparency, temperature, and pH. Result shown that the transparency was 24,33–25,83cm, temperature was 29-30°C, pH was 5, DIN was 0,31 - 0,39 mg/L, total phosphorus was 0,09-0,48 mg/L, oxygen saturation was 41,64-58,80 %, and chlorophyll-awas 3,09-7,93 µg/L.Trophic Index(TRIX) value of the Embung AKAP was4,79-5,29, and it can be categorized mesotrophic-eutrophic.Keywords :Vollenweider’s, Trophic Index, Water quality, Eutrophic, Mesotrophic